2022
DOI: 10.3390/ma15093050
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Microtensile Bond Strength, Film Thickness, and Microhardness of Photo-Polymerized Luting Composites

Abstract: The aim of this study was to evaluate the effect of CAD/CAM composite thickness on micro-tensile bond strength (µTBS), microhardness (HV), and film thickness (FT) of different luting composites. Composite blocks (6.8 mm × 6.8 mm) were divided into 12 groups according to: CAD/CAM thickness and luting composite. For each group, 21 rods (1 mm × 1 mm) were tested in tension at crosshead speed of 1 mm/min. Fracture modes were categorized as adhesive, mixed, and cohesive. Microhardness (n = 5/group) was assessed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…As a result, the first null hypothesis of no difference between the film thickness of DC‐ARC and PH‐RC, independently of the operator's expertise, must be rejected. This is in agreement with results found in previous studies 41,45,56 …”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…As a result, the first null hypothesis of no difference between the film thickness of DC‐ARC and PH‐RC, independently of the operator's expertise, must be rejected. This is in agreement with results found in previous studies 41,45,56 …”
Section: Discussionsupporting
confidence: 94%
“…This is in agreement with results found in previous studies. 41,45,56 Some authors have described differences in the flowability of composites when pre-heated at 37 or 69 C 31 while others have not observed such differences at 23, 54 or 68 C. 55 In this study, the highest heating temperature dispensed by the ENA-heat heater (55 C) was used. An under 10 s delay between the removal of the pre-heated cartridge and its use was carefully observed by the two operators, as important temperature drops have been shown passed delay.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Recently, a thermo-viscous photo-polymerized bulk ll resin composite was introduced (VOCO GmbH Germany) in order to get the advantages being applied in bulk and reducing viscosity for improving adaptation. To the best of our knowledge, only in a recent in vitro study [12], thermos-viscous bulk-ll resin composite was used as luting resin for CAD/CAM composite bonding. In this study, the authors suggested the use of such bulk-ll material as an alternative approach to dual-polymerized resin cement.…”
Section: Introductionmentioning
confidence: 99%